STRATEGIES FOR TEACHING ENGLISH GRAMMAR AND VOCABULARY TO NON-NATIVE SPEAKERS - Malokhatkhon Norboeva (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Teaching English grammar and vocabulary to non-native speakers requires a multifaceted and integrated approach. This article examines evidence-based strategies that educators can employ to support the development of learners’ grammatical accuracy and lexical competence.